Pension fund management, investment performance, and herding in the context of regulatory changes: New evidence from the Polish pension system - Łukasz Dopierała; Magdalena Mosionek-Schweda (Risks, 2021)
The aim of this paper is to assess the impact of reforms introduced in the operation of Polish open pension funds on management style, risk exposure and related investment performance. The article analyzes the impact of the reformed regulations on the herd behavior of fund managers. In particular, we examined whether the elimination of the internal benchmark for fund evaluation impacts the elimination or reduction of herd behavior. We proposed a multi-factor market model to evaluate the performance of funds investing in various types of instruments. Moreover, we used panel estimation to directly take into account the impact of the internal benchmark on herd behavior. Our results indicate that highly regulated funds may slightly outperform passive benchmarks and their unregulated competitors. In the case of Polish open pension funds, limiting investments in Treasury debt instruments clearly resulted in increased risk and volatility of returns. However, it also raised competition between funds and decreased the herd behavior. Additionally, the withdrawal of the mechanism evaluating funds based on the internal benchmark was also important in reducing herd behavior.
Keywords: 330; herd behavior; investment performance; pension funds; pension scheme design; regulatory reform